2016
DOI: 10.1111/ctr.12829
|View full text |Cite
|
Sign up to set email alerts
|

1,25 Dihydroxyvitamin D circulating levels, calcitriol administration, and incidence of acute rejection, CMV infection, and polyoma virus infection in renal transplant recipients

Abstract: Observation that 1,25-Dihydroxyvitamin-D3 has an immunomodulatory effect on innate and adaptive immunity raises the possible effect on clinical graft outcome. Aim of this study was to evaluate the correlation of biopsy-proven acute rejection, CMV infection, BKV infection, with 1,25-Dihydroxyvitamin-D3 deficiency and the benefit of calcitriol supplementation before and during the transplantation. Risk factors and kidney graft function were also evaluated. All RTRs received induction therapy with basiliximab, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 61 publications
(63 reference statements)
1
28
1
Order By: Relevance
“…Biological plausibility was supported by the dose‐response gradient observed between lower quartiles of serum 25(OH)D levels and infection susceptibility, with a 24% decrease in the risk of overall infection per each one‐quartile increase. Our results reinforce recent studies suggesting the clinical relevance of the immunomodulatory role attributable to vitamin D in the setting of ongoing immunosuppression after KT.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Biological plausibility was supported by the dose‐response gradient observed between lower quartiles of serum 25(OH)D levels and infection susceptibility, with a 24% decrease in the risk of overall infection per each one‐quartile increase. Our results reinforce recent studies suggesting the clinical relevance of the immunomodulatory role attributable to vitamin D in the setting of ongoing immunosuppression after KT.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, more than half of patients lacked vitamin D measurement . Finally, Moscarelli et al measured 1,25(OH) 2 D 3 (calcitriol) at post‐transplant months 1, 6 and 12 and observed a significant association between serum levels <20 pg/mL and the development of CMV or BK viremia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations